PENGARUH PEMAHAMAN KONSEP DAN SELF CREATIVITY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MELALUI SELF CONFIDENCE - Ani, Evi Wahyu Febriani; Nurdahlia, Dwi Ulfa (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Problem-solving ability is an important skill in science learning. This study aims to examine the influence of conceptual understanding and creativity on problem-solving ability, both directly and through self-confidence as an intervening variable. The study used an ex post facto quantitative approach with 59 sixth grade students as respondents, and data analysis was conducted using a path model. The results showed that conceptual understanding had a direct effect of 0.440 on problem-solving ability, while creativity had a direct effect of 0.396. When self-confidence was included as an intervening variable, the indirect effect of conceptual understanding was 0.326, while creativity was -0.187. These findings indicate that self-confidence can strengthen or weaken the relationship between conceptual understanding and creativity with problem-solving ability, so that strengthening students' self-confidence is an important aspect in science learning.